Construal level and free will beliefs shape perceptions of actors' proximal and distal intent - Plaks, Jason E.; Robinson, Jeffrey S. (Frontiers in Psychology, 2015)
Two components of lay observers’ calculus of moral judgment are proximal intent (the actor’s mind is focused on performing the action) and distal intent (the actor’s mind is focused on the broader goal). What causes observers to prioritize one form of intent over the other? The authors observed whether construal level (Studies 1-2) and beliefs about free will (Studies 3-4) would influence participants’ sensitivity to the actor’s proximal versus distal intent. In four studies, participants read scenarios in which the actor’s proximal and distal intent were independently manipulated. In Study 1, when only distal intent was present in the actor’s mind, participants rated the psychologically distant actor more responsible than the psychologically near actor. In Study 2, when only distal intent was in the actor’s mind, participants with a chronic high level of action identification rated the actor more responsible than did those with a low level of action identification. In both studies, when only proximal intent was in the actor’s mind, construal level did not predict judgments of responsibility. In Study 3, when only proximal intent was present in the actor’s mind, the more participants believed in free will, the more they rated the actor responsible. When only distal intent was in the actor’s mind, free will belief did not influence ratings of responsibility. In Study 4, the same pattern emerged when free will / determinism beliefs were manipulated and the actor performed a positive (life-saving) act. The authors discuss how these results shed new light on the literatures on moral reasoning and psycho-legal theory.